BPSK Receiver Based on Adaptive Structure with Remodulation - Dimitrijevic, B.; Milosevic, N.; Nikolic, Z. (Elektronika ir Elektrotechnika, 2011)
In this paper we propose a binary phase shift keying (BPSK) signal receiver, where the reception is performed by a new complexadaptive structure with remodulation (R-ATF) which does not require the exact knowledge of the carrier frequency. Therefore, thisreceiver does not have a phase-locked loop (PLL), and it has a fixed frequency oscilator with frequency equal to the expected inputsignal frequency. The proposed structure is created by modifying a complex adaptive transversal filter with the introduction of signalremodulation, and it uses least mean squares (LMS) algorithm for its weights adaptation. The main feature of this receiver is that it hasperformances that are close to the performances of the BPSK receiver with an ideal extraction of the reference carrier for a wide rangeof frequency offsets of practical importance between the input signal and the fixed frequency reference carrier in the receiver. Ill. 5, bibl.8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.620